Renova Museum: a project to revitalize the Casal de Monte Redondo Museum (Cadernos de Sociomuseologia, 2022)
With a brief historical contextualization about Museu do Casal de Monte Redondo this work presents and analyse the participative project “Renova Museu: Revitalização de um museu por meio de ações educativas” (“Renova Museu”: Revitalization of a museum by educational actions), awarded in context of IX Ibermuseus Education Award in 2018 and developed in 2019. On a closely and critical approach, such as the relation between practices and academy in it context, it will be detailed the stages management at project development, it potentialities, it failures, it precepts, it adaptations, it partnerships, it multiple collectives, it persons.Keywords: Sociomuseology; Renova Museu; Community Museum; Education; Ibermuseus